Período anterior à interferência de corda-de-viola em cana-planta - Piza, Caio Spada de Toledo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Sugarcane has undergone a major change in the environment with the adoption of mechanized harvesting. One of the changes resulting from the presence of straw on the ground was the change in weed profile. In this scenario Ipomoea hederifolia L. grown in importance. The presence of this weed in the areas of mechanical harvesting can contribute to the occurrence of infestations after the reform of the sugarcane plantation. There is still no information about the interference that this kind of morningglory can have on cane plant cycle. The aim of this study was to determine the Period Prior to Interference (PAI) of a weed community that contains I. hederifolia as the main weed in relation to sugarcane variety 'SP81-3250’ in the cane plant cycle. Moreover, the goal was to determine the possible loss of productivity change and technological parameters (Pol and ATR). Phytosociological analysis of the weed community was performed with determination of parameters relative density (Der), relative frequency (FeR), relative dominance (DoR), importance value index (IVI) and relative importance (IR) with the objective to confirm the predominance of mornigglory. The experimental treatments consisted of increasing periods of presence in the early sugarcane cycle with a weed community with predominance of mornigglory, namely: 0, 0-15, 0-30, 0-45 , 0-60, 0-75, 0-90, 0- 120, 0-150, 0-180, 0-210, 0-270, 0-330 days after emergence. It was used a randomized block design with four replications. The test was conducted in the field, getting sowing I. hederifolia. Also, selective weeding were performed. The phytosociological analysis showed that the community possessed predominance of mornigglory. The data showed that the PAI of mornigglory (I. hederifolia) relative to sugarcane 'SP81-3250' in the cane plant cycle was 76 days, with a level 5% for acceptable loss. The loss of productivity of industrialized stalks due to ...

A cana-de-açúcar sofreu uma grande alteração em seu ambiente de produção com a adoção da colheita mecanizada. Uma das mudanças resultantes da presença de palha sobre o solo foi a alteração do perfil de plantas daninhas. Neste cenário Ipomoea hederifolia L. cresceu em importância. A presença desta planta daninha nas áreas de colheita mecanizada pode contribuir para a ocorrência de infestações após a reforma do canavial. Ainda não há informações sobre a interferência que esta espécie de corda-de-viola pode exercer sobre a cana-deaçúcar no ciclo de cana-planta. O objetivo deste trabalho foi determinar o período anterior à interferência (PAI) de uma comunidade infestante que contivesse I. hederifolia como principal planta daninha em relação à cana-de-açúcar variedade ‘SP81-3250” no ciclo de cana-planta. Além disso, houve o objetivo de determinar a possível perda de produtividade e alteração dos parâmetros tecnológicos (Pol e ATR). Foi realizada análise fitossociológica da comunidade de plantas daninhas, com determinação dos parâmetros densidade relativa (Der), frequência relativa (FeR), dominância relativa (DoR), índice de valor de importância (IVI) e importância relativa (IR) tendo por objetivo confirmar a predominância de corda-de-viola. Os tratamentos experimentais constaram de períodos crescentes de convivência no início do ciclo da cana-de-açúcar com uma comunidade de plantas daninhas com predominância de corda-de-viola, a saber: 0, 0-15, 0-30, 0-45, 0-60, 0-75, 0-90, 0- 120, 0-150, 0-180, 0-210, 0-270, 0-330 dias após a emergência. Foi utilizado delineamento blocos ao acaso com quatro repetições. O ensaio foi realizado em campo, recebendo semeadura de I. hederifolia. Ainda, foram realizadas mondas seletivas. A análise fitossociológica demonstrou que a comunidade possuiu predominância de corda-de-viola. Os dados permitiram concluir que o período anterior à interferência ...
Keywords: Cana-de-açúcar; Erva daninha; Produtividade agrícola; Competição (Biologia); Convolvulacea; Sugar-cane